Les techniques actuelles de contrôle démocratique et de participation aux choix énergétiques généraux au Québec - Garant, Patrice (Les Cahiers de droit, 1983)
Techniques of democratic control and public participation in general energy choices have recently been the concern of many, especially in Quebec. Firstly, over the last ten years, the Parliamentary Committee on Energy and Resources has been the forum of important debates and serious discussions. Members of the National Assembly have been able to follow to a certain extent the rapid evolution of energy policies and to articulate the concerns of the general public. Those responsible for Crown corporations (Hydro, SOQUIP) have had to account for their projects and to report regularly. Through public hearings, various economic agents have had the opportunity to present their views on many occasions. The second important technique, the use of an indépendant regulatory agency, in this case, the Quebec Gas and Energy Board, with a rather limited jurisdiction, has been the centre of discussions. Some see in that formula an adequate channel of public participation ; others have some hesitation about accepting the broadening of the role of an indépendant regulatory agency, where important issues have to be dealt between the Minister and major Crown corporations.